The effect of synaptic plasticity on orientation selectivity in a balanced model of primary visual cortex - Gonzalo Cogno, Ximena Soledad; Mato, German (Frontiers Media S.A., 2015)
Fil: Gonzalo Cogno, Ximena Soledad. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina